Relations between the Home Learning Environment and the Literacy and Mathematics Skills of Eight-Year-Old Canadian Children - Sheri-Lynn Skwarchuk; Heather Douglas; Abbie Cahoon; Jo-Anne LeFevre; Chang Xu; Emilie Roy; Victoria Simms; Judith Wylie; Erin A. Maloney; Helena P. Osana; María Inés Susperreguy (MDPI AG, 2022)
The home learning environment includes parental activities, attitudes, affect, knowledge, and resources devoted to supporting children's development, including literacy and mathematics skills. These factors are related to the academic performance of preschool children (aged 3 to 6 years), before formal schooling and possibly beyond. In the present research, we examined the home learning environment of Canadian families as reported by either the mother (n = 51) or father (n = 30) of their Grade 3 child (n = 81; Mage = 8.7 years; range 8 to 9 years of age). Importantly, mothers' and fathers' reports of the home learning environment for school children were similar. For literacy, parents' knowledge of children's books and attitudes toward literacy were related to children's vocabulary skills; home literacy was not related to word reading skills. For mathematics, parents' reports of the frequency of activities such as practicing arithmetic facts and their attitudes toward mathematics were related to children's arithmetic fluency. Other aspects of the home learning environment (time spent helping with homework, parents' math anxiety) were not related to children's performance. These results suggest some continuity between home learning environments and academic skills after children's transition to school.